PENGARUH KUALITAS PRODUK, DESAIN PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TUPPERWARE DI KOTA PONTIANAK - B11110089, HENDRIKUS CLASSOLALIA (Jurnal Manajemen Update, 2015)
This study aimed to analyze whether the variables of the quality of product, product design, and brand image have impact on the customer purchase decision toward product Tupperware. This study was designed as an explanatory study. Population of the study was customers of product Tupperware in Pontianak. The sampling technique used was purposive sampling, namely 100 respondents as the total number of samples in Pontianak city. The analysis technique used was multiple linear regression analysis using SPSS version 22.0. the result of data analysis showed that the quality of product, product design, and brand image, both partially and simultaneously, have positive and significant impact on customer purchase decision toward product Tupperware in Pontianak city with a significance value of 0.000 and R2 value of 46.6% while the remaining 54.4% are the other factors which were not investigated in this study. Keywords: quality of product, product design, brand image, and purchase decision